Effects of NH3 pulse plasma on atomic layer deposition of tungsten nitride diffusion barrier - Lee, CW; Kim, YT (A V S AMER INST PHYSICS, 2006)
We deposited W-N thin films on Si and tetraethylorthosilicate (TEOS)/Si substrates at 200-400 degrees C, synchronizing a pulse plasma only with NH3 exposure cycles during atomic layer deposition (ALD) cycles of NH3 and WF6. The deposition rate was about 0.3 nm/cycle at 350 degrees C, the nitrogen concentration was uniformly distributed in the W-N films, and the NH3 pulse plasma did not cause wormholes at the Si surface. However, there was an incubation period to deposit the W-N film according to the ideal ALD mechanism. Rutherford backscattering spectroscopy revealed that a 22-nm-thick W-N thin film, as a diffusion barrier for the Cu interconnect, successfully prevented the Cu diffusion during the annealing at 600 degrees C for 30 min. (c) 2006 American Vacuum Society.
Keywords: FILMS; SILICON